Gradually European and Diminishingly Balkan - Zlatan Krajina (Annales, Series Historia et Sociologia)
This paper explores the cultural representation of Croatia in international guidebooks published during the process of the country’s EU-accession (2003–2013). Using a qualitative textual analysis of how the introductions’ narratives in the guidebooks depicted Croatia, this study recognises the dynamic interplay of aspects from European and Balkan identity. The country was constructed as a mobile destination, moving from the Balkans into “Europe”. Croatia’s developing tourist infrastructure was highlighted to describe the country as gradually becoming “European”. Simultaneously, there was a reduction in the explicit reference to the country’s Balkan identity, its peripheral location and transitional culture. I describe this representational strategy of ongoing and incomplete movement as “controlled proximity”.